Design of a Web-Based Church Notice Board System Using the Waterfall Method - Bertrandus Iffan Pradhana; Penidas Fiodinggo Tanaem (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
This study designs a web-based church announcement board system using the Waterfall method to improve communication effectiveness compared to physical bulletin boards. The system was developed using PHP, MySQL, HTML, CSS, and JavaScript through stages of requirement analysis, design, implementation, and black box testing. It introduces features for uploading weekly bulletins and dynamic announcement management, accessible directly by church members via a browser. The implementation results show a reduction in announcement publishing time from 2 hours to 4 minutes and a 75% decrease in administrative workload. Black box testing on 7 scenarios confirmed that all core features, such as login, announcement management, and bulletin uploads, functioned as expected. The page load time averaged 1.2 seconds, with responsive performance on mobile devices and a p95 response time of 480 ms for 100 concurrent users. This study contributes to the digitalization of church information, providing a more efficient, interactive, and real-time system, thereby enhancing information accessibility for the congregation.